Pengaruh Kedisiplinan Manajemen Perawatan Terhadap Kinerja Mesin Kapal - Sugeng Haryadi; Renny Hermawati; Kundori (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
In the maritime industry, ship engine performance is highly dependent on disciplined and structured maintenance management. This study aims to analyze and understand in depth the relationship between the level of discipline in maintenance management and the performance of merchant ship engines in the national shipping industry. This causes decreased engine efficiency, increased fuel consumption, and technical damage that impacts shipping safety and financial losses. This study uses a qualitative approach with observation and interview methods in several ship units. Data collection was carried out using several techniques, namely in-depth interviews, participatory observation, and documentation studies. The results show that maintenance carried out in a disciplined manner can increase operational efficiency and reduce the risk of engine damage. Ships with high discipline show more stable performance, good fuel efficiency, and minimal operational downtime. Meanwhile, undisciplined ships experience more damage and disruptions in shipping schedules. It is concluded that discipline in carrying out ship engine maintenance schedules has a significant effect on engine performance.